(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
Toxoplasma gondii is an opportunistic pathogen that can kill congenitally infected fetuses, newborns, and immunocompromised patients by reactivating a latent infection. The aim of study knowing the extent of Toxoplasma effect of on the level of IL-17 in SLE patient. In this study, 250 blood samples from both genders female and male were collected. Using the ELISA technique, T. gondii immunoglobulins (IgG and IgM) antibodies and (IL-17) levels were assessed in all serum samples. According to the findings of this investigation, SLE patients had the greatest rate of toxoplasmosis infection. The percentage of anti-Toxoplasma IgG (50%) was higher than the percentage of anti-Toxoplasma IgM (4%), across all groups. IL-17 was highly in SLE and Toxoplasma infected patient (151.87 ± 5.99). These result is suggested that direct pro-inflammatory activity, may have a role in SLE pathogenesis. Toxoplasmosis must be diagnosed and treated in SLE patients in order to lessen the impact of the illness because most immunocompromised people are exposed to a number of possible risk factors, including Toxoplasma original infection or reactivation